Highly Tunable Elastomeric Silk Biomaterials. (22nd April 2014) - Partlow, Benjamin P.; Hanna, Craig W.; Rnjak‐Kovacina, Jelena; Moreau, Jodie E.; Applegate, Matthew B.; Burke, Kelly A.; Marelli, Benedetto; Mitropoulos, Alexander N.; Omenetto, Fiorenzo G.; Kaplan, David L.
<x xml:space="preserve">Abstract</x> Elastomeric, fully degradable, and biocompatible biomaterials are rare, with current options presenting significant limitations in terms of ease of functionalization and tunable mechanical and degradation properties. A new method for covalently crosslinking tyrosine residues in silk proteins, via horseradish peroxidase and hydrogen peroxide, to generate highly elastic hydrogels with tunable properties, is reported. These materials offer tunable mechanical properties, gelation kinetics, and swelling properties. In addition, these new polymers withstand shear strains on the order of 100%, compressive strains greater than 70% and display stiffness between 200–10 000 Pa, covering a significant portion of the properties of native soft tissues. Molecular weight and solvent composition allow control of material mechanical properties over several orders of magnitude while maintaining high resilience and resistance to fatigue. Encapsulation of human bone marrow derived mesenchymal stem cells (hMSC) shows long term survival and exhibits cell‐matrix interactions reflective of both silk concentration and gelation conditions. Further biocompatibility of these materials is demonstrated with in vivo evaluation. These new protein‐based elastomeric and degradable hydrogels represent an exciting new biomaterials option, with a unique combination of properties, for tissue engineering and regenerative medicine.